The university- society in Honduras and their contribution to society transformer - Molina Zavala, Ariel Fabricio; Martínez-Andrades, Erick (Rev. iberoam. bioecon. cambio clim., 2016)
The general purpose of this article is to analyze the advances and contributions of the University-society relationship developed by higher education institutions in the Republic of Honduras. This relationship is not only part of the training of professionals or administrative areas, but also in those activities, projects and productive, scientific and academic programs that have the Honduran university as its main promoter. In this sense, higher education institutions in Honduras have successfully faced and overcome the different stages and social moments that have marked the history of this young republic. A yes then the university as an institution has been in great way, responsible for the formation of human resources; responsible for the social and economic development of society as a whole.